Study of ossicular chain status in chronic otitis media patients at a tertiary care hospital in southern Bihar - Sinha, Ankita; Singh, Garima; Pandey, Ranbir K.; Gupta, Deepak K.; Diwakar , Chandrakant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: The objective is to assess the ossicular status and statistically evaluate the extent of ossicular destruction intraoperatively in chronic otitis media (COM) patients. Knowledge of pattern of involvement of ossicular chain in COM cases may help us to determine the type of reconstruction needed during surgery. The findings of this study could be exploited to predict preoperatively the probability of having ossicular chain destruction in COM ears and thus patients could therefore be properly consented about these potential issues before surgery. Methods: Prospective observational study conducted over 2 years in diagnosed patients posted for surgical management and fulfilling the inclusion criteria. Intraoperative status of ossicles was noted for various types of COM and outcome was evaluated. Results: Out of 92 patients, 59 (64.1%) had mucosal and 33 (35.9%) had squamosal disease. Ossicular chain was eroded in 41 cases (44.6%). 9 out of 59 (15.3%) mucosal cases and 32 out of 33 squamosal cases (97%) reported ossicular erosion. Most frequently involved was long process of incus (44.6%) >stapes (9.8%) >malleus (8.7%). Order of involvement (Austin-Kartush classification) was found as: type A (26.1%)>B (9.8%)>C (8.7%). 67.4% belonged in the group 15-30 years. Male: female ratio=1:1.5. Conclusions: Degree of ossicular destruction is much greater in squamosal COM, owing to overproduction of cytokines and inflammatory mediators and due to presence of cholesteatoma and/or granulations. The long process of incus was found to be most vulnerable. Malleus was found to be the most resilient among all ossicles.